Revealing the Utilization of Pragma-dialectics and Fallacies in BongBong Marcos Supporters' Facebook Argumentations - Cyra Godessa Largado; Ma. Saine Arranguez; Yacint Cahumna; Joemar Turno Minoza (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
In this modern era, most transactions occur online, including the management of disputes. However, argumentation in the context of social media is rarely articulated in detail. Intuitively, people may recognize flaws in argumentation but may not be entirely certain about them. Hence, this research evaluates the reasonableness and effectiveness of online argumentation, particularly among Bongbong Marcos' supporters, as significant opposition exists due to his 2022 Philippine presidential candidacy. One example analyzed is De La Salle University's written unity statement posted on their Facebook page. Discourse analysis was employed to examine the data. Results show that Bongbong Marcos' supporters in the argumentative activity are not strategic in constructing their standpoint, as they distort critical discussion stages and commit fallacious arguments, failing to attain crucial stages of the evaluation process. Thus, Bongbong Marcos' supporters are not strategic in their arguments.